Antihepatocarcinoma Effect of Portulaca oleracea L. in Mice by PI3K/Akt/mTOR and Nrf2/HO-1/NF-κB Pathway - Guoyin, Zheng (Evid Based Complement Alternat Med, 2017)
The purpose of the present study was to evaluate the pharmacological effects of Portulaca oleracea L. (Purslane) (PL) on N-nitrosodiethylamine- (NDEA-) induced hepatocellular carcinomas (HCC) and explore its potential mechanism. Mice were randomly assigned to four groups: control group, NDEA group, NDEA + Purslane (100 mg/kg) group, and NDEA + Purslane (200 mg/kg) group. The animal of each group was given NDEA (100 ppm) in drinking water. 1 h later, Purslane dissolved in PBS was intragastrically administered for continuous seven days. The results showed that Purslane reduced the activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in liver and serum. Purslane also reduced the contents of interleukin-6 (IL-6), IL-1β, tumor necrosis factor-α (TNF-α), and methane dicarboxylic aldehyde (MDA) and restored the activity of superoxygen dehydrogenises (SOD) in serum. Purslane could obviously attenuate the hepatic pathological alteration. Furthermore, treatment with Purslane effectively inhibited the phosphorylations of phosphatidylinositol 3 kinase (PI3K), protein kinase B (Akt), mammalian target of rapamycin (mTOR), nuclear factor-kappa B (NF-κB), and inhibitor of NF-κBα (IκBα) and upregulated the expressions of NF-E2-related factor 2 (Nrf2) and heme oxygenase- (HO-) 1. In conclusion, our research suggested that Purslane exhibited protective effects on NDEA-induced hepatocellular carcinomas by anti-inflammatory and antioxidative properties via the PI3K/Akt/mTOR and Nrf2/HO-1/NF-κB pathway.